Atomically Precise Water‐Soluble Graphene Quantum Dot for Cancer Sonodynamic Therapy (Adv. Sci. 19/2022). Issue 19 (6th July 2022) - Ju, Yang‐Yang; Shi, Xiao‐Xiao; Xu, Shu‐Yu; Ma, Xiao‐Hui; Wei, Rong‐Jing; Hou, Hao; Chu, Cheng‐Chao; Sun, Di; Liu, Gang; Tan, Yuan‐Zhi
Abstract : Graphene Quantum Dots An atomically‐precise graphene quantum dot with bilayer stacking (structures shown in cover picture) is synthesized and monodispersed in water owing to introducing sterically hindered water‐soluble functional groups. Under the ultrasonic irradiation, it can generate abundant cellular reactive oxygen species (detected as the green fluorescence of cells shown as the background of the cover picture), and thus shows excellent tumor inhibition potency. More details can be found in article number 2105034 by Gang Liu, Yuan‐Zhi Tan, and co‐workers.